Phosphoinositide lipid phosphatase SHIP1 and PTEN coordinate to regulate cell migration and adhesion - Mondal, Subhanjan (The American Society for Cell Biology, 2012)
The second messenger phosphatidylinositol(3,4,5)P(3) (PtdIns(3,4,5)P(3)) is formed by stimulation of various receptors, including G protein–coupled receptors and integrins. The lipid phosphatases PTEN and SHIP1 are critical in regulating the level of PtdIns(3,4,5)P(3) during chemotaxis. Observations that loss of PTEN had minor and loss of SHIP1 resulted in a severe chemotaxis defect in neutrophils led to the belief that SHIP1 rather than PTEN acts as a predominant phospholipid phosphatase in establishing a PtdIns(3,4,5)P(3) compass. In this study, we show that SHIP1 regulates PtdIns(3,4,5)P(3) production in response to cell adhesion and plays a limited role when cells are in suspension. SHIP1((−)/(−)) neutrophils lose their polarity upon cell adhesion and are extremely adherent, which impairs chemotaxis. However, chemotaxis can be restored by reducing adhesion. Loss of SHIP1 elevates Akt activation following cell adhesion due to increased PtdIns(3,4,5)P(3) production. From our observations, we conclude that SHIP1 prevents formation of top-down PtdIns(3,4,5)P(3) polarity to facilitate proper cell attachment and detachment during chemotaxis.